Judge Peer Effects in the Courthouse - Ozkan Eren; Naci Mocan (Institute of Labor Economics (IZA), 2020)
Although there exists a large literature analyzing whether an individual's peers have an impact on that individual's own behavior and subsequent outcomes, there is paucity of research on whether peers influence a person's decisions and judgments regarding a third party. We investigate whether consequential decisions made by judges are impacted by the gender composition of these judges' peer group. We utilize the universe of decisions on juvenile defendants in each courthouse in Louisiana between 1998 and 2012. Leveraging random assignment of cases to judges, and variations in judge peer composition generated by elections, retirements, deaths and resignations, we show that an increase in the proportion of female peers in the courthouse causes a rise in individual judges' propensity to incarcerate, and an increase in the assigned sentence length. This effect is fully driven by female judges. We also demonstrate that the impact of proportion of female peers is not a proxy for other peer characteristics such as race and age. Further analysis suggests that this behavior of female judges is unlikely to be a reflection of an effort to conform to evolving norms of judicial stringency, measured by peers' harshness in sentencing, but that it is due to the sheer exposure to female colleagues.
Keywords: D9; K4; 330; peers; judicial; harshness; leniency; sentencing; judge; critical mass; juveniles; crime; court